Identification of a Rab GTPase-activating protein cascade that controls recycling of the Rab5 GTPase Vps21 from the vacuole - Rana, Meenakshi (Mol Biol Cell, 2015)
Transport within the endocytic pathway depends on a consecutive function of the endosomal Rab5 and the late endosomal/lysosomal Rab7 GTPases to promote membrane recycling and fusion in the context of endosomal maturation. We previously identified the hexameric BLOC-1 complex as an effector of the yeast Rab5 Vps21, which also recruits the GTPase-activating protein (GAP) Msb3. This raises the question of when Vps21 is inactivated on endosomes. We provide evidence for a Rab cascade in which activation of the Rab7 homologue Ypt7 triggers inactivation of Vps21. We find that the guanine nucleotide exchange factor (GEF) of Ypt7 (the Mon1-Ccz1 complex) and BLOC-1 both localize to the same endosomes. Overexpression of Mon1-Ccz1, which generates additional Ypt7-GTP, or overexpression of activated Ypt7 promotes relocalization of Vps21 from endosomes to the endoplasmic reticulum (ER), which is indicative of Vps21 inactivation. This ER relocalization is prevented by loss of either BLOC-1 or Msb3, but it also occurs in mutants lacking endosome–vacuole fusion machinery such as the HOPS tethering complex, an effector of Ypt7. Importantly, BLOC-1 interacts with the HOPS on vacuoles, suggesting a direct Ypt7-dependent cross-talk. These data indicate that efficient Vps21 recycling requires both Ypt7 and endosome–vacuole fusion, thus suggesting extended control of a GAP cascade beyond Rab interactions.